Research and Development dalam Media Pembelajaran Game Flash Adventure Quiz pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas VII SMP - Asmad , Zulfah Nur Risky; Nasir, Nasir; Andi Adam , Andi Adam (Program Pascasarjana, UIN Alauddin Makassar, 2023)
The main problem in this study (1) how the process of learning media development and (2) how the media learning flash adventure quiz-based Adobe Flash cs6 game on subjects IPA in junior high unismuh makassar can be worth to use. The study aims to (1) know the results of learning media development and (2) know the feasibility of media game adventure-based Adobe Flash cs6 on the flash quiz subjects IPA in junior high unismuh makassar. The study is this type of research development r&d (research & development) by using addie model that is analysis, design, development, implementation, and evaluation. The development procedure consists of several stages that is, potential analysis and problems, design storyboards image, the preparation of the material and assessment instruments for experts, the creation of learning media products, media assessment by validators, the application of the small scale trials and media evaluation of learning. The application of the trial in doing in junior laboratory unismuh makassar involving students that add up to 20 people Class VII. Based on the development that has been implemented in mind that: (1) results learning media products in the form of game called adventure quiz, with the format of type exe program with the solar system for junior high school Class VII subject matter IPA (2) the results from the media expert and expert material against the media learning game adventure quiz categorized is very good and decent use. Abstrak Masalah utama dalam penelitian ini yaitu (1) bagaimana proses pengembangan media pembelajaran dan (2) bagaimana media pembelajaran game flash adventure quiz berbasis adobe flash CS6 pada mata pelajaran IPA di SMP Unismuh Makassar dapat layak untuk digunakan. Penelitian ini bertujuan untuk (1) mengetahui hasil pengembangan media pembelajaran dan (2) mengetahui kelayakan media game flash adventure quiz berbasis adobe flash CS6 pada mata pelajaran IPA di SMP Unismuh Makassar. Penelitian ini merupakan jenis penelitian pengembangan R&D (Research & Development) dengan menggunakan model ADDIE yaitu Analysis, Design, Development, Implementation, dan Evaluation. Prosedur pengembangan terdiri dari analisis potensi dan masalah, desain gambar storyboard, penyusunan materi dan instrumen penilaian untuk para ahli, pembuatan produk media pembelajaran, penilaian media oleh validator, penerapan uji coba skala kecil dan evaluasi media pembelajaran. penerapan uji coba di lakukan di laboratorium SMP Unismuh Makassar yang melibatkan siswa yang berjumlah 20 orang kelas VII. Berdasarkan hasil pengembangan yang telah dilaksanakan diketahui bahwa: (1) hasil produk media pembelajaran berupa game bernama adventure quiz, dengan format program bertipe exe dengan materi pelajaran IPA tata surya untuk SMP kelas VII (2) hasil penilaian dari ahli media dan ahli materi terhadap media pembelajaran game adventure quiz dikategorikan sangat baik dan layak digunakan.